The Influence Of Social Media Marketing And Information Quality On The Decision To Use The Bibit Investment Application Among Students - Nadia Adindra; Maulana Agung P; Jamingatun Hasanah (Cita konsultindo, 2025)
The value of saving and investing for the future is becoming more widely recognized, especially because the future is full of uncertainties. Preparing for future needs through investment has become a wise step increasingly recognized by society, especially among the youth. The research fills a gap in the literature regarding digital investment application usage, particularly focusing on students who are active users of social media and digital technologies. The data was analyzed using SPSS, and 86 respondents were surveyed using a quantitative research procedure that employed explanatory research. The results indicate that the decision to use the Bibit application is significantly influenced by both information quality and social media marketing. Specifically, social media marketing influences users' decision-making by providing educational content and up-to-date investment information, while information quality, including the relevance and timeliness of the provided content, plays a crucial role in users' satisfaction. These results offer valuable insights